Diplomatic relations between Iraq and Czechoslovakia 1958 - 1968 (Journal of the College of Basic Education, 2024)
Diplomacy is one of the most important means of foreign policy and its implementation tool in managing international relations. Therefore, researchers and specialists in international law consider it one of the most prominent foundations of global peace and security. On this basis, this study is concerned with the diplomatic representation and foreign policy of an emerging country such as the Republic of Iraq. Some circumstances must be taken into account. Political decision-making, especially with regard to foreign policy, including specifically diplomatic representation between Iraq with its two systems (monarchy and republic) and the Czechoslovak Republic, and understanding the outcome of establishing political relations with the countries of the Eastern bloc, especially Czechoslovakia. The nature of the research required it to be divided into three axes. The first axis was entitled The Historical Roots of Iraqi-Czechoslovak Diplomatic Relations Before 1958, the second axis was titled Iraqi-Czechoslovak Diplomatic Relations 1958-1963, and the third